The Strategy of School Principal to Promote Multicultural Education in Islamic High Schools in Samarinda - Muchammad Eka Mahmud (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Multicultural education is the process of character formation for respecting and valuing different groups such as ethnicity, culture, language, race, and skin color because human nature is created for mutual recognition. The purpose of this research is to explore the school principal strategies in promoting multicultural education at one of the Islamic high schools in Samarinda, East Kalimantan, Indonesia. This research employed a case study design with a qualitative approach. Direct observation was done to make sure the implementation of multicultural education in the process of teaching and learning in classrooms. Additionally, in-depth interview was conducted with three types of school elements including the school principal, four vice principals, and two representative teachers to figure out their perspectives towards the implementation of multicultural education so far at their school as well as figure out the strategies used by the school principal. Document analysis was also utilized in order to make sure the reflection of multicultural education values on the teaching materials used by teachers in class. The results showed that the school principal apply contribution and enrichment strategies in applying multicultural education at school. It was discovered that multicultural education was reflected in all three aspects, i.e., teaching materials, students’ activities, and the teaching and learning process. The research novelty and future implications of this study are further discussed in this article.